Birds. - Mohamad Fizl Sidq, Ramji; Wen Teng, Ng; Hilda Jelembai, Neilson Ilan; Standley Bawin, Bunsi; Isa, Sait; Rahah, Mohd Yakup; Nur Nadhirah Izzaty, Selamat (Sarawak Forestry Corporation and Natural History Publications (Borneo), Kota Kinabalu., 2022)
Birds are useful bioindicators for monitoring ecological change. They form an interactive community within the ecosystem and are integral for pollination and seed dispersal for many native plants (Gatesire et al., 2014; Stratford et al., 2015). Nonetheless, the destruction of avian habitats, such as lowland forests for timber, human settlements and coastal development in recent decades have resulted in the decline of many avian species (Kihia, 2014; Barlow et al., 2016). Little work has been done on the mangroves and coastal birds in Sarawak, despite increasing threats towards such ecosystems (Wilson, 2002)